Parasitosis in Pet Dogs from Rondônia, Amazon Biome, and Human Perception of Zoonoses - Mendonça, Talita Oliveira [UNESP]; Perin, Patricia Parreira [UNESP]; Zanini, Dayane da Silva [UNESP]; de Souza, Hortência Laporti; Pires, Paulo Henrique Kanopp; Muniz, Igor Mansur; Tebaldi, José Hairton [UNESP]; Mathias, Luís Antonio [UNESP]; Bürger, Karina Paes [UNESP]; Lux-Hoppe, Estevam G. [UNESP] (MDPI, 2024)
Zoonotic parasitic diseases in dogs are particularly concerning in regions with low human development indices due to inadequate sanitary services and insufficient environmental and health education. This study aimed to assess the parasitological status of dogs living in households and evaluate their owners’ knowledge about zoonoses. A total of 183 dogs from Rolim de Moura, Rondônia State, were screened for the presence of ectoparasites, and 163 fecal samples were collected for analysis. The results showed that 74.23% (112/163) of the animals had at least one species of endoparasite. The most identified pathogens were Ancylostoma spp. (68.71%, 112/163), Trichuris vulpis (11.66%, 19/163), Toxocara canis (6.75%, 11/163), Cystoisospora canis (4.91%, 8/163), Dipylidium caninum (1.23%, 2/163), and Hammondia/Neospora (0.61%, 1/163). Ectoparasites were observed in 43.17% (79/183) of the evaluated animals, with Rhipicephalus sanguineus found in 31.15% (57/183) and Ctenocephalides felis felis in 20.77% (38/183). Only 11.48% (7/61) of the owners were familiar with the term “Zoonoses.” However, a significant majority (83.61%, 51/61) believed that dogs can transmit diseases to humans. Our findings highlight the prevalence of parasites in the studied area and associated risk factors, underscoring the urgent need for educational interventions to raise awareness about these diseases and their risks to human health.
Keywords: ectoparasites; endoparasites; one health; zoonoses